High resolution U-Pb ages of Ca-phosphates in Apollo 14 breccias: Implications for the age of the Imbrium impact - Merle, Renaud; Nemchin, Alexander; Grange, Marion; Whitehouse, M.; Pidgeon, Robert (John Wiley & Sons, Inc., 2014)
Previous age estimates of the Imbrium impact range from 3770 to 3920 Ma, with the latter being the most commonly accepted age of this basin-forming event. The occurrence of Ca-phosphates in Apollo 14 breccias, interpreted to represent ejecta formed by this impact, provides a new opportunity to date the Imbrium event as well as refining the impact history of the Moon. We present new precise U-Pb analyses of Ca-phosphates from impact breccia sample 14311 that are concordant and give a reliable weighted average age of 3938 ± 4 Ma (2σ). Comparison with previously published U-Pb data on phosphate from Apollo 14 samples indicate that all ages are statistically similar and suggest phosphates could have been formed by the same impact at 3934 Ma ± 3 Ma (2σ). However, this age is older than the 3770 to 3920 Ma range determined for other samples and also interpreted as formed during the Imbrium impact. This suggests that several impacts occurred during a 20–30 Ma period around 3900 Ma and formed breccias sampled by the Apollo missions.